Perícia ambiental e análise estatística de parâmetros influenciadores de infrações ambientais - Cunha, Danilo Jorge Evangelista (2019)
Due to the increasing development of new technologies, urban growth and urbanization, more and more the environment has been exploited by anthropic action, in many occasions this human intervention can cause negative impacts. Hence the need for the Public Power to create mechanisms for the defense and protection of environmental resources, such as the Brazilian environmental legislation that provides for this type of crime, as well as the importance of qualified professionals to conduct examinations in places where alleged environmental crimes occurred, are environmental experts, specialists in several areas of human knowledge who prepare reports that will assist Justice in clarifying crimes against the environment, these illicit ones can cause infractions by environmental institutions such as Brazilian Institute Environment and Renewable Resources and State Superintendence of the Environment, for example, in the Metropolitan Region of Fortaleza, in the present experiment, we searched for the factors or parameters that most influenced the incidence of environmental infractions, with emphasis on numerical parameters. To that end, experts were interviewed in the area and analyzed the factors that all reported in common, population, Gross Domestic Product and number of active industries, through Pearson's correlation coefficient, of dispersion charts, where there was a strong association between the selected parameters and the incidence of environmental infractions. In addition, by calculating weights through the coefficient of variation maps can be made to observe the spatial distribution of each factor selected and how much each contributes to the occurrence of environmental infractions in each municipality of the study area, the Region Fortaleza, Maracanaú and Caucaia, there is a reduction of the environmental infractions as of the weights of each selected factor, population, economy and industries in the phenomena of the environmental infractions. It was also verified the existence of non-numerical factors that influence the mentioned phenomenon, and that they are also of great relevance, such as the concentration of environmental professionals in the big urban centers and the insufficiency of environmental inspectors in the public service.